2018
DOI: 10.1021/acs.macromol.7b02756
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Relaxation of Poly(styrene-co-butadiene) Chains at Substrate Interface in Spin-Coated and Solvent-Cast Films

Abstract: The local conformation of poly(styrene-co-butadiene) rubber (SBR) chains in direct contact with a quartz substrate was examined by interface-sensitive sum-frequency generation (SFG) spectroscopy. SFG signals, which could be obtained from functional groups only oriented at the interface, were clearly observed for SBR in a film at room temperature which was much higher than the bulk glass transition temperature (T g ). When the film was thermally annealed, SBR chains at the quartz interface changed their conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 80 publications
(128 reference statements)
2
26
0
Order By: Relevance
“…Hence, it can be claimed that the relaxation of the SFG peaks is directly connected to the intrinsic dynamics of chains in the strongly adsorbed layer. 42 Similarly, we also reported that PI chains in direct contact with the SiO 2 surface were relaxed at (T g b + 125) K. 41 Although the adsorbed PI chains were fully relaxed with increasing temperature up to (T g b + 130) K, 41 such a full relaxation was not here observed for adsorbed NBR chains. At 423 K, (∼(T g b + 180) K), while the SFG peaks corresponding to different CH stretching vibration modes decreased, the peak arisen from CN groups increased, as shown in Figure 3.…”
mentioning
confidence: 72%
“…Hence, it can be claimed that the relaxation of the SFG peaks is directly connected to the intrinsic dynamics of chains in the strongly adsorbed layer. 42 Similarly, we also reported that PI chains in direct contact with the SiO 2 surface were relaxed at (T g b + 125) K. 41 Although the adsorbed PI chains were fully relaxed with increasing temperature up to (T g b + 130) K, 41 such a full relaxation was not here observed for adsorbed NBR chains. At 423 K, (∼(T g b + 180) K), while the SFG peaks corresponding to different CH stretching vibration modes decreased, the peak arisen from CN groups increased, as shown in Figure 3.…”
mentioning
confidence: 72%
“…These results indicate the tangential orientation of the phenyl rings in immediate contact with the NP surface, which gradually decreases as the radial distance increases. 62 67 As a matter of fact, the styrene chains in the interfacial region expose mainly their phenyl rings to the NP ( Figure 7 c). Interestingly, even though the torsion of the styrene segment is only considered a representing torsion of the segment, the orientational order parameter S for the SSBR/TESPT-PIL composite model requires greater separation to reach the average bulk value ( S = 0) than that in the SSBR/TESPT composite model at the same temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, these techniques lack general monolayer surface and interfacial selectivity and sensitivity. Over the past three decades, sum frequency generation (SFG) vibrational spectroscopy has proven to be a powerful technique to directly and nondestructively study polymer surfaces/interfaces due to its inherently surface/interfacial specific selectivity and sensitivity, and its capability to provide molecular level structural information in situ. SFG has been used extensively to characterize molecular structures at buried polymer/solid or polymer/liquid interfaces. ,, In this study, we push the boundaries of SFG to systematically analyze chemical reactions at the buried polymer/polymer interface of nylon and maleic-anhydride grafted polyethylene.…”
Section: Introductionmentioning
confidence: 99%